The Roma struggle for compensation in post-war Germany - Knesebeck, Julia von dem 1979- (University of Hertfordshire Press, 2011)
Thirty years passed before it was accepted & mdash;in West Germany and elsewhere & mdash;that the Roma (Gypsies) of Germany had been Holocaust victims. Drawing upon a substantial body of previously unseen sources, this record examines the history of the Roma struggle for recognition as racially persecuted victims of National Socialism in postwar Germany. Looking at West Germany in the period between the end of the war and the beginning of the Roma civil rights movement in the early 1980s, this authoritative analysis demonstrates how pejorative attitudes continued unchallenged and how compensation was eventually achieved